Humanisme Freudian dan Pandangannya tentang Agama - Mudji Sutrisno (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
Freud’s psychoanalytic influence extends beyond psychology, significantly impacting philosophy by introducing a fundamental understanding of human nature, shaped by unconscious impulses. This paper explores Freud’s contributions to philosophy, particularly his perspectives on human nature and religion. By analyzing his theories, we aim to understand how his psychoanalytic framework redefined traditional views on religious belief and human existence.